Towards a Software Tool for Planning IHE-Compliant Information Systems. - Staubert, S.; Strubing, A.; Drepper, J.; Bergh, B.; Winter, A.; Merzweiler, A. (Stud Health Technol Inform, 2019)
As hospital information systems are complex and the requirements for interoperability grow with the increasing networking in healthcare, careful planning becomes more and more necessary. The use of standards as described in IHE profiles, for example, are an important prerequisite for enabling interoperability. Enterprise Architecture Planning (EAP) methods should support this, but none of the currently available EAP methods offers the option of using IHE profiles. The 3LGM2IHE project wants to close this gap and implement the support of IHE profiles in the 3LGM(2) tool. This paper describes how requirements for this tool were determined and presents the results.
Keywords: Delivery of Health Care; *Hospital Information Systems; *Software; *Systems Integration